Transactional Management, Transformational Leadership, Organizational Culture, and Teaching Competencies of Teachers in Basic Education - Risonar, Cupid Jones; Prado, Nenita; Digamon, Jayson (JPAIR Institutional Research, 2023)
There are concerns about teachers’ pedagogical competencies in the Philippines due to reports of poor performance by Filipino students in various academic disciplines. Studies show that teaching has more impact than other factors like services, facilities, and even leadership. Therefore, this study examined the teaching competencies of elementary school teachers, and sought which among transactional management, transformational leadership, and organizational culture are its best predictor/s. Questionnaires, in the form of hard copies and Google Forms, were used as data collection tools after undergoing rigorous scientific testing to ensure accuracy and consistency. Using Raosoft sample size calculator and reliability guidelines (Howard, 2016), this research study gathered information from 479 primary school teachers in two divisions: Gingoog City and Misamis Oriental. They were chosen using a proportionate stratified random technique. As implied by the results, it has been observed that teachers possess remarkable teaching competencies when planning, developing, and achieving desired outcomes. In addition, the teaching competencies of elementary teachers are significantly influenced by the levels of transactional management and transformational leadership exhibited by the school head, as well as the organizational culture they foster. They also demonstrate high confidence in their ability to impact student learning, effectively handle classroom management, actively engage in continuous professional development, and implement effective teaching strategies. The top predictors are cultural strength, achieving goals under organizational culture, and developing and changing under transformational leadership. All these predictors have a positive and direct impact on teaching competencies, which means that when these variables’ levels increase.